2016
DOI: 10.1016/j.molonc.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Biglycan stimulates VEGF expression in endothelial cells by activating the TLR signaling pathway

Abstract: Biglycan (BGN) is an important component of the extracellular matrix (ECM) that is impli-cated in a variety of human cancers. In our previous study, we reported that BGN was overexpressed in gastric cancer (GC) tissues and promoted cancer metastasis. Moreover, the tubular formation capacity in HUVECs was promoted by stimulation with culture media from BGN-overexpressing GC cells, but the exact underlying mechanism is still unknown.The purpose of this study was to determine the role and molecular mechanism of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
91
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 35 publications
3
91
1
Order By: Relevance
“…Most of the literature suggests that the primary role of TLR4 in angiogenesis is to enhance VEGF expression (11,12,34,35,42). In our study, MAP4K4 was discovered working downstream of TLR4 in a VEGF-independent pattern and played a role in regulating migration and proliferation in HRMECs.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Most of the literature suggests that the primary role of TLR4 in angiogenesis is to enhance VEGF expression (11,12,34,35,42). In our study, MAP4K4 was discovered working downstream of TLR4 in a VEGF-independent pattern and played a role in regulating migration and proliferation in HRMECs.…”
Section: Discussionmentioning
confidence: 52%
“…TLR4 is expressed in a diverse array of cells outside the immune system, and plays important roles in tissuespecific inflammation (28). TLR4 in endothelial cells contributes to angiogenesis as demonstrated in many systems, including sepsis-induced inflammatory angiogenesis in the lung (10), coculture systems of outgrowth endothelial cells and primary human osteoblasts (11), angiogenesis in cancer (12,13,33), rheumatoid arthritis (34), and recovery from brain injuries (35). TLR4 activation has reportedly resulted in ocular vascular abnormality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BGN is involved in various aspects of cancer biology, including cancer cell proliferation, invasion [38], epithelial-mesenchymal transition [39], angiogenesis [40], chemotherapy resistance [23], and patient prognosis [41], but the role of BGN during the early stages of cancer has not yet been elucidated. BGN expression is increased in many cancers including bladder cancer [39], colorectal cancer [42], gastric cancer [43], esophageal cancer [44], prostate cancer [40], and endometrial cancer [45] and various factors modulate its expression, including p38 [46], HIF-1 [47], TGF-β/Smad4 [48], and NF-κB [26]. NF-κB may serve a crucial factor at the early stage of colorectal cancer progression, and we demonstrated that it may play a crucial role in the regulation of BGN gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Biglycan (BGN) is a member of small leucine-rich proteoglycans family, and it has been ascribed a pivotal role in oncogenesis and development of various other types of human cancer. It is also an important component of the extracellular matrix 9 . BGN is found in almost every organ in a non-uniform distribution pattern within human body.…”
Section: Introductionmentioning
confidence: 99%